Clinical, haematological and biochemical effects of detomidine and ketamine anaesthesia in dogs - JADON, N S; KUMAR, AMRESH; SINGH, HARNAM; SINGH, HARPAL (The Indian Journal of Animal Sciences, 2013)
Intramuscular administration of detomidine (0.2 mg/kg) followed by ketamine (5 mg/kg) in atropine sulphate (0.04 mg/kg) premedicated dogs (12) resulted in onset of anaesthesia in 6.4±2.3 min. The duration of anaesthesia lasted for 41.30±5.35 min and recovery occurred in 62.60±5.60 min. There was a significant (P